The World book encyclopedia. - World Book, Inc. (Chicago : World Book, 1991)
An encyclopedia designed especially to meet the needs of elementary, junior high, and senior high school students.
Spine title: World book.
Vols. 23-24 have subtitle: Britain & Ireland.
Includes bibliographical references and index.
Keywords: Encyclopedias and dictionaries; Encyclopedias and dictionaries